Carregando nas costas: a constituição racial do direito do trabalho brasileiro e a movimentação de corpos negros - Barbara Almeida Duarte (2024)
The history of Brazilian society is the history of the movement of black bodies. In a broad sense, we can say that black people moved, serving as a support base for the construction, and currently maintenance, of the country; in a strict sense, many black men and women were, and continue to be, responsible for the movement of goods and people. But there is also a sense of resistance, which we can extract from the black movement in its struggles against slavery and for improvements in working conditions. However, Labor Law tells us that none of this concerns them, as enslaved people did not work, did not fight and all others did not exist, since they were not subjects. But, as we will see, there are elements that allow us to challenge this narrative that was chosen to appear as history. As for the present, we intend to talk about a specific category, that of loose non-port loaders who load and move goods in Supply Centers. Regulated by special legislation that states that their relationship is not one of employment, they work in locations normally far from urban centers, experiencing day-to-day non-compliance with health and safety standards and the special legislation that regulates them. Today, at risk of even losing coverage under partial legislation, the category is attacked in the National Congress by a bill that emerged a few months ago, which states that the work carried out by porters is autonomous. However, the arrival point of the analysis is based on many assumptions regarding the movement of black bodies in Brazilian history…